Analisis Pengembangan Kurikulum dan Materi PAI melalui Program Literasi Keagamaan sebagai Upaya Peningkatan Mutu Pendidikan Madrasah - Mayasari, Annisa (Lembaga Sosial Rumah Indonesia, 2023)
The objective of this research is to analyze the development of the curriculum and materials for Islamic Religious Education (PAI) through a religious literacy program to improve the quality of education in madrasahs. This study utilizes a qualitative approach with a literature review and descriptive methods supported by a philosophical-pedagogical approach. The development of the PAI curriculum and materials through the religious literacy program encompasses four main components: objectives, content, methods, and evaluation. The program aims not only to enhance students' interest in reading but also to train them in critiquing sources of knowledge and values related to religion. The development of the PAI curriculum and materials through the religious literacy program has positive implications for improving the quality of education in madrasahs.